From jobs to careers: drivers and barriers to career development in emerging labor markets - Luwei, Wang; Huimin, Ma (Frontiers in Sociology, 2024)
IntroductionThis study aims to reveal the intrinsic and extrinsic drivers of career development in emerging labor markets and to explore the impact of these drivers and barriers on career development. With the rapid transformation of global industrial structure, career development in emerging industries such as artificial intelligence, big data, new energy and e-commerce is gradually attracting attention.MethodsThis study utilizes a mixed research method of questionnaires and in-depth interviews. The research team distributed a total of 700 questionnaires to practitioners in China, the United States, Japan, Germany and India, and collected interview data from 20 industry practitioners. These data were analyzed from both quantitative and qualitative perspectives to analyze the drivers and barriers to career development, and structural equation modeling was used to analyze the relationship between career motivation, barriers, social networks, and career satisfaction.ResultsThe results indicate that career development motivation significantly and positively influences career satisfaction, while individuals with high career satisfaction perceive fewer career barriers. In addition, career barriers significantly influenced individuals’ perceptions of career discrimination. The study also found that social networks play an important supportive role in career development, and that extensive social networks increase career satisfaction. Individuals with high motivation were more resilient in the face of external barriers and were willing to retrain to improve their occupational skills.DiscussionTo promote career development in emerging industries, labor market policies should optimize and create fair and inclusive work environments for emerging industries. By eliminating gender, age, and racial discrimination and providing employee support programs, career development satisfaction and opportunities can be effectively enhanced.ConclusionRapid technological updates, high work pressure, and cross-cultural barriers in emerging industries are the main challenges to career development today. This study suggests that governments and enterprises should jointly provide flexible vocational training and support policies to help practitioners adapt to the rapidly changing occupational environment.